Trançado D’Contadores: histórias sertanejas e os desdobramentos da oralidade (re)memorada - Freitas, Jhonatan Barbosa de (2024)
In the city of Choró – CE, Cafundó is a non-village community of indigenous descent where there are breaths of survival, welcome and belonging, resisting the passing of the years. Residents construct/pass on stories orally, weaving causes and tales, desires and traditions. Narratives take us to various experiences, but, above all, to a particular way of perceiving/understanding the world. Among the descendants who left the community was my grandfather, who, for years during my childhood, told stories about those who live “on top of the mountains”. Aiming to corroborate the verbal poetics of (re)memoration, activated through affection, the research presents, based on literature, W. Benjamin (1994), H. Bergson (1999), S. Freud (1936), J. Larrosa (2002), L. Martins (2003), P. Nora (1993), Kastrup (2007) and many others, as well as through the short “A genesis from above: A story not written” (2017), (with)together with the narratives “Grandfather’s Dream” and “Marmota”, and through my artistic developments, how the verb becomes powerful through affective memories/remembrances, in how an ancestry can also take root through the simple act of being. The dissertation also aims to understand how a memory can be filled with forgetfulness, as Ailton Krenak (2023) points out, leaving voids and unsaid, in what should be the most private, subjective and firm of social constructs, our memorized ancestry. The voice, embodied, imagery, gains traces and reincorporates a latent past that insists on not being forgotten, as perceptible in the various actions that have as their central landmark the mythology of the “Marmota”, this memorable being that is present in much of the second moment of writing. The experiments carried out, the desires put into practice, in this artistic becoming, corroborate the objective, to become Being. The work was (in)completed successfully, still leaving spaces for listening, believing, creating, (re)creating , according to the most disparate affections.